A RESEARCH ON ROLE OF MUSEUMS IN URBAN CONSERVATION: SAMPLE OF MARDİN MUSEUM - Evindar YEŞİLBAŞ (Fırat University, 2019)
Looking at the historical development of museums, it can be observed that due to the data they obtain, they have an effective role in defining social life practices of the term and economic, political conditions and socio-cultural understanding. Museum with an educational institution's mission, at the same time it is an obligation work so as to make up an organic tie with the society to improve urban identity and memory, and awareness of protection. In the complex historical urban societies that are about to disappear it is becoming more and more noticeable that organic ties are necessary and obligatory. Urban museums are defined especially by International Committee of Collection of City Museums and Activities which is a sub-committee of ICOM as “a museum model that aims to improve and strenghten the city identity in a planned way which reflects the past, present and future of the city ”. As it can also be understood from the definition, especially city museums are dynamic institutions in terms of strenghtening the participation process of important actors (citizens) and in order to keep historical continuity going on. In this framework in our study, it will be made clear with cocrete data how Mardin Museum plays a role in projections related to future besides reflecting the past of the city. Studies done in the sense of protecting the historical urban identity with the reproduction-retransformation projects of incredients that make up of the urban planning and urban identity of Mardin Museum with an awareness to protect historical urcan area and urban identity will be discussed. In this study, first of all the history of Mardin Museum’s background will be given .In second part, some information about the studies that Mardin Museum has completed and its future projects will be mentioned. In the conclusion of study the assessment of the mentioned projects and studies will be with a critical method. Furthermore, several recommendations will be presented for the protection of urban spaces. In this study it is aimed to create a functional awareness of the role of museums in cities that have a historical identity. It is thought that by presenting the studies which Mardin Museum carried out in the urban conservation area, it will set an example for similar applications in Turkey in terms of keeping the historical incredients that make up of the city alive.